Elevated mRNA-levels of distinct mitochondrial and plasma membrane Ca2+ transporters in individual hypoglossal motor neurons of endstage SOD1 transgenic mice - Mühling, Tobias; Duda, Johanna; Weishaupt, Jochen H.; Ludolph, Albert C.; Liss, Birgit (Frontiers in Cellular Neuroscience, 2014)
Disturbances in Ca2+ homeostasis and mitochondrial dysfunction have emerged as major pathogenic features in familial and sporadic forms of Amyotrophic Lateral Sclerosis (ALS), a fatal degenerative motor neuron disease. However, the distinct molecular ALS-pathology remains unclear. Recently, an activity-dependent Ca2+ homeostasis deficit, selectively in highly vulnerable cholinergic motor neurons in the hypoglossal nucleus (hMNs) from a common ALS mouse model, endstage superoxide dismutase SOD1G93A transgenic mice, was described. This functional deficit was defined by a reduced hMN mitochondrial Ca2+ uptake capacity and elevated Ca2+ extrusion across the plasma membrane. To address the underlying molecular mechanisms, here we quantified mRNA-levels of respective potential mitochondrial and plasma membrane Ca2+ transporters in individual, choline-acetyltransferase (ChAT) positive hMNs from wildtype (WT) and endstage SOD1G93A mice, by combining UV laser microdissection with RT-qPCR techniques, and specific data normalization. As ChAT cDNA levels as well as cDNA and genomic DNA levels of the mitochondrially encoded NADH dehydrogenase ND1 were not different between hMNs from WT and endstage SOD1G93A mice, these genes were used to normalize hMN-specific mRNA-levels of plasma membrane and mitochondrial Ca2+ transporters, respectively. We detected about 2-fold higher levels of the mitochondrial Ca2+ transporters MCU/MICU1, Letm1 and UCP2 in remaining hMNs from endstage SOD1G93A mice. These higher expression-levels of mitochondrial Ca2+ transporters in individual hMNs were not associated with a respective increase in number of mitochondrial genomes, as evident from hMN specific ND1 DNA quantification. Normalized mRNA-levels for the plasma membrane Na2+/Ca2+exchanger NCX1 was also about 2-fold higher in hMNs from SOD1G93A mice. Thus, pharmacological stimulation of Ca2+ transporters in highly vulnerable hMNs might offer a novel neuroprotective strategy for ALS.